2020
DOI: 10.3389/fped.2020.00267
|View full text |Cite
|
Sign up to set email alerts
|

Immediate Post-operative Enterocyte Injury, as Determined by Increased Circulating Intestinal Fatty Acid Binding Protein, Is Associated With Subsequent Development of Necrotizing Enterocolitis After Infant Cardiothoracic Surgery

Abstract: Objectives: 1 Measure serial serum intestinal fatty acid binding protein levels in infants undergoing cardiac surgery with cardiopulmonary bypass to evaluate for evidence of early post-operative enterocyte injury. 2 Determine the association between immediate post-operative circulating intestinal fatty acid binding protein levels and subsequent development of necrotizing enterocolitis. Design: Observational cohort study. Intestinal fatty acid binding protein was measured pre-operatively, at rewarming, and at 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Normal turnover of small intestinal enterocytes releases low levels of IFABP into the plasma, but much higher plasma levels of IFABP suggest significant disruption of the small intestinal villi [ 39 ]. While also proposed as a biomarker for classical NEC [ 113 , 114 ], circulating IFABP measured 6 h postoperatively has successfully predicted cardiac NEC development in infants undergoing CPB [ 115 ]. However, in a prospective study, Pathan et al found that elevated IFABP, either pre- or postoperatively, poorly predicted clinical outcomes in pediatric CHD cases [ 39 ].…”
Section: Potential Biomarkers For Cardiac Necmentioning
confidence: 99%
“…Normal turnover of small intestinal enterocytes releases low levels of IFABP into the plasma, but much higher plasma levels of IFABP suggest significant disruption of the small intestinal villi [ 39 ]. While also proposed as a biomarker for classical NEC [ 113 , 114 ], circulating IFABP measured 6 h postoperatively has successfully predicted cardiac NEC development in infants undergoing CPB [ 115 ]. However, in a prospective study, Pathan et al found that elevated IFABP, either pre- or postoperatively, poorly predicted clinical outcomes in pediatric CHD cases [ 39 ].…”
Section: Potential Biomarkers For Cardiac Necmentioning
confidence: 99%
“…Thus, FABP-2 can be used for early detection ( 34 ). High levels of FABP-2 were found in infants following cardiopulmonary bypass indicating early enterocyte injury that potentially increases the risk of NEC ( 35 ). The FABP-2 assay in this study used umbilical blood immediately after birth, reflecting perinatal conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Fecal calprotectin and intestinal fatty acid binding protein may become useful laboratory biomarkers for NEC [ 59 , 60 ]. Doppler ultrasonography of the mesenteric vessels and abdominal aortic blood flow in diastole may be increasingly used as a predictive strategy, which could increase vigilance among practitioners [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…In an observational cohort study of 120 infants undergoing cardiopulmonary bypass, intestinal fatty acid binding protein was measured at 6 and 24-h post-surgery. Significantly higher levels were noted in patients who subsequently developed NEC [ 60 ].…”
Section: Preventative Strategiesmentioning
confidence: 99%